Different Effects of Structured Education on Glycemic Control and Psychological Outcomes in Adolescent and Adult Patients with Type 1 Diabetes: A Systematic Review and Meta-Analysis - Fang Liu; Yuzhu Guan; Xia Li; Yuting Xie; Jing He; Zhi-Guang Zhou; Lezhi Li (International Journal of Endocrinology)
Aim. This systematic review aimed at investigating the effectiveness of structured education (SE) in improving glycemic control and psychological outcomes in adolescent and adult patients with type 1 diabetes. Methods. Electronic databases (EMBASE, Medline, PubMed, and the Cochrane Library) and the reference lists of included studies were searched from the beginning of the database through April 2019. Randomized controlled trials comparing SE with a control condition and reporting a change in glycosylated hemoglobin (HbA1c) level were included. The primary outcome was glycemic control measured by HbA1c. Secondary outcomes were diabetes-related distress, well-being, depression, and quality of life. Results. Eighteen studies representing 2759 patients were included. Twelve studies targeted adolescents and six targeted adults. Adolescent patients who were randomized to the intervention group did not show significant improvement of HbA1c in the short (SMD = −0.04; 95% CI: −0.14 to 0.06; P=0.41), medium (SMD = −0.03; 95% CI: −0.13 to 0.07; P=0.55), and long term (SMD = 0.04; 95% CI: −0.16 to 0.25; P=0.66) or of diabetes self-efficacy (SMD = −0.17; 95% CI: −0.33 to 0.00; overall effect P=0.05). However, SE was effective in reducing HbA1c levels in adult patients with inadequate baseline control (HbA1c higher than 7.5%) (SMD = −0.52; 95% CI: −0.86 to −0.17; P=0.003). SE significantly improved the well-being and psychological distress of adult patients but had no effect on the extent of depression. Conclusions. Development of more efficient SE programs according to the patients’ personal characteristics is needed.